Membangun e-trust mahasiswa melalui e-service quality dan e-satisfaction mahasiswa - Salamatun Asakdiyah; Deny Ismanto (Jurnal Konseling dan Pendidikan, 2022)
This study aims to examine the effect of E-Service Quality, E-Satisfaction and the interaction between E-Service quality and E-Satisfaction in the building of E-Student Trust at the management  Study Programm Faculty of Economics and Business, Ahmad Dahlan University in Yogyakarta. Sample categorized with sampling convenience method and purposive sampling. Data Collection efforted by giving list of question to the respondent that is contains about E-Service Quality, E-Satisfaction, and E-trust. This research use Moderator Regression Analysis (MRA). In the other side, T Test and F-Test are used to the asked hypothesis. This result of partially regression coefficience test with T test shows that E-Service Quality, E-Satisfaction, also interaction between them influence significantlyto E-Student Trust. In the other side coefficien regression with F test is result shows that variable of E-Service Quality, E-Satisfaction also interaction between them in the influence to E-Trust. Variable of E-Service Quality, E-Satisfaction also interaction between them are able to explain E-Trust variable up 75,9% and the rest is 24,1% caused by another variable that is not included in the research model.